Perception of Climate Change and Pro-Environmental Behavioral Intentions of Forest Recreation Area Users—A Case of Taiwan - Chang, Min-Yen; Kuo, Hung-Yu; Chen, Han-Shen (Forests, 2022)
This study aims to extend the theory of planned behavior to explore climate change perception, adaptation intention, and behavioral patterns of PEB of tourists in the Xitou Nature Education Area (XNEA) in Taiwan. Furthermore, we analyzed the correlation among various variables using partial least squares structural equation modeling (PLS-SEM). Data were collected from the close-ended question questionnaires; sample size (n = 626). SPSS 22.0 and AMOS 22.0 for Windows were used as tools for analysis. The results are as follows: the perception of tourists on climate change exerts a significant positive effect on attitudes, subjective norms, and perceived behavioral control, which, in turn, exerts significant positive effects on climate change adaptation intentions. Furthermore, climate change adaptation intentions exert a significant positive influence on the behavioral patterns of PEB. Finally, political trust exerts a moderating effect on the relationship between subjective norms and climate change adaptation intentions and between perceived behavioral control and climate change adaptation intentions. Our findings indicate that it is necessary to encourage awareness of climate change, and that it is also very important to increase the value of political trust when making environmental policies.